Safety and efficacy of alternative antibiotic regimens compared with 7 day injectable procaine benzylpenicillin and gentamicin for outpatient treatment of neonates and young infants with clinical signs of severe infection when referral is not possible: a randomised, open-label, equivalence trial. Issue 5 (May 2015) - Baqui, Abdullah H; Saha, Samir K; Ahmed, A S M Nawshad Uddin; Shahidullah, Mohammad; Quasem, Iftekhar; Roth, Daniel E; Samsuzzaman, A K M; Ahmed, Wazir; Tabib, S M Shahnawaz Bin; Mitra, Dipak K; Begum, Nazma; Islam, Maksuda; et al.
Summary Background Severe infections remain one of the main causes of neonatal deaths worldwide. Possible severe infection is diagnosed in young infants (aged 0–59 days) according to the presence of one or more clinical signs. The recommended treatment is hospital admission with 7–10 days of injectable antibiotic therapy. In low-income and middle-income countries, barriers to hospital care lead to delayed, inadequate, or no treatment for many young infants. We aimed to identify effective alternative antibiotic regimens to expand treatment options for situations where hospital admission is not possible. Methods We did this randomised, open-label, equivalence trial in four urban hospitals and one rural field site in Bangladesh to determine whether two alternative antibiotic regimens with reduced numbers of injectable antibiotics combined with oral antibiotics had similar efficacy and safety to the standard regimen, which was also used as outpatient treatment. We randomly assigned infants who showed at least one clinical sign of severe, but not critical, infection (except fast breathing alone), whose parents refused hospital admission, to one of the three treatment regimens. We stratified randomisation by study site and age (<7 days or 7–59 days) using computer-generated randomisation sequences. The standard treatment was intramuscular procaine benzylpenicillin and gentamicin once per day for 7 days (group A). The alternative regimens were intramuscular gentamicin once per day and oral amoxicillin twice per day for 7 days (group B) or intramuscular procaine benzylpenicillin and gentamicin once per day for 2 days, then oral amoxicillin twice per day for 5 days (group C). The primary outcome was treatment failure within 7 days after enrolment. Assessors of treatment failure were masked to treatment allocation. Primary analysis was per protocol. We used a prespecified similarity margin of 5% to assess equivalence between regimens. This study is registered with ClinicalTrials.gov, number NCT00844337. Findings Between July 1, 2009, and June 30, 2013, we recruited 2490 young infants into the trial. We assigned 830 infants to group A, 831 infants to group B, and 829 infants to group C. 2367 (95%) infants fulfilled per-protocol criteria. 78 (10%) of 795 per-protocol infants had treatment failure in group A compared with 65 (8%) of 782 infants in group B (risk difference −1·5%, 95% CI −4·3 to 1·3) and 64 (8%) of 790 infants in group C (−1·7%, −4·5 to 1·1). In group A, 14 (2%) infants died before day 15, compared with 12 (2%) infants in group B and 12 (2%) infants in group C. Non-fatal relapse rates were similar in all three groups (12 [2%] infants in group A vs 13 [2%] infants in group B and 10 [1%] infants in group C). Interpretation Our results suggest that the two alternative antibiotic regimens for outpatient treatment of clinical signs of severe infection in young infants whose parents refused hospital admission are as efficacious as the standard regimen. This finding could increase treatment options in resource-poor settings when referral care is not available or acceptable. Funding USAID, WHO, Save the Children-US, and Bill & Melinda Gates Foundation.